1997
DOI: 10.1080/15216549700201951
|View full text |Cite
|
Sign up to set email alerts
|

Protease triggers dephosphorylation of cdc2 kinase during starfish oocyte maturation

Abstract: Summary: We previously presented evidence that a Z-Phe-Ser-argininal-susceptible protease which is involved in oocyte maturation of the starfish, Asterina pectinifera is the proteasome (Takagi Sawada et al., Dev. BioL 150, 414-418 (1992)). In the present study, we investigated the timing of the function of and the role of the protease in oocyte maturation using Z-Phe-Ser-argininal. By adding the inhibitor in maturing oocytes at various times after 1-methyladenine treatment, the inhibitory ability was markedly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In toad and starfish oocytes, inhibition of proteasomal proteolytic activity prevented GV breakdown (GVBD) [19,20]. Inhibition of GVBD was also observed with microinjection of antiproteasome ␣ subunit antibodies into the starfish oocytes [21][22][23][24].…”
Section: Introductionmentioning
confidence: 72%
“…In toad and starfish oocytes, inhibition of proteasomal proteolytic activity prevented GV breakdown (GVBD) [19,20]. Inhibition of GVBD was also observed with microinjection of antiproteasome ␣ subunit antibodies into the starfish oocytes [21][22][23][24].…”
Section: Introductionmentioning
confidence: 72%
“…In 2-, 3-, and 4-cell embryos, the localization of ubiquitin protein could be detected in the nucleus (F-L). Murray et al, 1989;Sawada et al, 1997;Suzumori et al, 2003;Takagi Sawada et al, 1997;Takahashi et al, 1994;Tokumoto et al, 1997), our understanding of the roles and the regulatory mechanisms of UPP in mammalian oocyte meiosis, fertilization and early embryonic mitosis was limited.…”
Section: Discussionmentioning
confidence: 99%
“…CPEB is degraded coincident with GVBD, which occurs ϳ4 h into the ϳ6-h maturation process. To avoid perturbing early events in maturation that may require proteasome activity (Sawada et al, 1997), we attempted to block CPEB degradation by injecting inhibitors into oocytes in which maturation had been initiated but had not yet advanced to GVBD. We found that non-GVBD oocytes taken from a batch of maturing oocytes where 50% had achieved GVBD (GVBD 50 ) were suitable for these studies.…”
Section: Cpeb Is Degraded By the Proteasome Pathwaymentioning
confidence: 99%